Molecular and morphological analyses revealed a cryptic species of dojo loach Misgurnus anguillicaudatus (Cypriniformes: Cobitidae) in Japan - R. Okada; T. Inui; Y. Iguchi; T. Kitagawa; K. Takata; T. Kitagawa (Journal of Fish Biology, 2017)
Although it has been reported that populations of the Japanese dojo loach Misgurnus anguillicaudatus (Cypriniformes: Cobitidae) belong to two distinct mitochondrial (mt)DNA (Type I and Type II), the taxonomic status of the species remains unresolved. To address this question, nuclear DNA and morphological analyses were performed on M. anguillicaudatus population in the Nakaikemi Wetland, where Type I and Type II lineages are sympatric. Results suggest the existence of a cryptic species (Type I) within the Japanese dojo loach.

Evaluation of the safety and efficacy of Glycyrrhiza uralensis root extracts produced using artificial hydroponic and artificial hydroponic-field hybrid cultivation systems - H. Akiyama; M. Nose; N. Ohtsuki; S. Hisaka; H. Takiguchi; A. Tada; N. Sugimoto; H. Fuchino; T. Inui; N. Kawano; S. Hayashi; A. Hishida; et al. (Journal of Natural Medicines, 2017)

Population pharmacokinetics of tacrolimus in adult recipients receiving living-donor liver transplantation - Fukatsu S.; Yano I.; Igarashi T.; Hashida T.; Takayanagi K.; Saito H.; Uemoto S.; Kiuchi T.; Tanaka K.; Inui K. (European Journal of Clinical Pharmacology, 2001)

Structure, expression and products of the ribosomal RNA operons of Rhodopseudomonas palustris No. 7 - K. Zahn; M. Inui; H. Yukawa (Molecular Genetics and Genomics, 2001)

Cloning and expression of yellowtail ascites virus segment A - H. Sato; E. Emoto; T. Kamata; H. Mori; K. Kamei; A. Kitaoka; R. Takano; K. Nakajima; Y. Inui; K. Kudo; S. Hara (Archives of Virology, 1999)

Pharmacokinetics and pharmacodynamics of acetazolamide in patients with transient intraocular pressure elevation - I. Yano; A. Takayama; M. Takano; M. Inatani; H. Tanihara; Y. Ogura; Y. Honda; K. Inui (European Journal of Clinical Pharmacology, 1998)